The OPTION trial: inhibition of the interleukin-6 receptor with tocilizumab in patients with rheumatoid arthritis. Issue 5 (October 2008) - Ramos-Remus, Cesar; Muriel-Vizcaino, Rodolfo
Rheumatoid arthritis (RA) is a disease that patients may suffer for decades. RA is a complex syndrome with an increasing number of cell types, cellular mediators and signaling pathways implicated in the inflammatory networks of the disease. Interleukin (IL)-6 is a proinflammatory cytokine. Thus, targeting IL-6 has a biological congruence as a therapeutic option in RA patients. Tocilizumab is a humanized monoclonal antibody that binds to the IL-6 receptor. A study to assess the effect of tocilizumab in 622 patients with moderate-to-severe active RA (OPTION) was a Phase III, three-arm, randomized, double-blind, placebo-controlled study. Efficacy was assessed using standard composite criteria (ACR, EULAR) at 24 weeks. Safety was assessed at regular intervals during the study. A 70% improvement according to the ACR (ACR70) was achieved in more patients treated with tocilizumab than with placebo. Higher responses were seen in the tocilizumab high-dose group than in the tocilizumab low-dose group. The most common adverse events were infections. Blocking IL-6 is a novel therapeutic approach that could be effective in moderate-to-severe active RA patients. The long-term efficacy and safety profile of tocilizumab remains to be determined.